2019
DOI: 10.1523/eneuro.0349-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Imaging of Parvalbumin Neurons in the Dorsal Root Ganglia

Abstract: We investigated the calcium dynamics of dorsal root ganglion (DRG) neurons using transgenic mice to target expression of the genetically encoded calcium indicator (GECI), GCaMP6s, to a subset of neurons containing parvalbumin (PV), a calcium-binding protein present in proprioceptors and low-threshold mechanoreceptors. This study provides the first analysis of GECI calcium transient parameters from large-diameter DRG neurons. Our approach generated calcium transients of consistent shape and time-course, with qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It has been reported that PV is co-expressed with neurotrophin-3 and tyrosine receptor kinase C proteins, which are associated with the development of proprioceptive receptors and their primary afferent neurons ( Ernfors et al, 1994 ). Furthermore, it has been mentioned that about 90 % of PV-ir DRG neurons are proprioceptors ( de Nooij et al, 2013 ; Wralters et al, 2019 ). In addition, another calcium-binding protein CR is also regarded as a potential marker for proprioceptors, although it is expressed in a very small sub-population (10 %) of medium-large-sized DRG neurons ( Ren et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PV is co-expressed with neurotrophin-3 and tyrosine receptor kinase C proteins, which are associated with the development of proprioceptive receptors and their primary afferent neurons ( Ernfors et al, 1994 ). Furthermore, it has been mentioned that about 90 % of PV-ir DRG neurons are proprioceptors ( de Nooij et al, 2013 ; Wralters et al, 2019 ). In addition, another calcium-binding protein CR is also regarded as a potential marker for proprioceptors, although it is expressed in a very small sub-population (10 %) of medium-large-sized DRG neurons ( Ren et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…2C1) 2426 . We used a genetic strategy to target DRG neurons that express parvalbumin, which are proprioceptors 27, 28 . In transgenic rats that express Cre recombinase under the control of parvalbumin promoter PV-Cre rats (LE-Tg(Pvalb-iCre)2Ottc), we injected a Cre-dependent DREADD (AAV5-hSyn-DIO-hM4D(Gi)-mCherry 29 into the C5, C6, and C7 DRGs as described above (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For the second strategy, we targeted the proprioceptive afferents for inactivation, since these mediate the effects of spinal cord stimulation (Takeoka et al, 2014;Asboth et al, 2018). We used a genetic strategy to target DRG neurons that express parvalbumin, which are proprioceptors (Ichikawa et al, 1994;Walters . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted December 8, 2020. ; https://doi.org/10.1101/2020.12.07.398289 doi: bioRxiv preprint et al, 2019).…”
Section: Afferent Inactivation (Fig 3)mentioning
confidence: 99%
“…2 Ai) or the creation of transgenic mice selectively expressing GECIs in neuronal sub-populations ( Fig. 2 Aii) ( Jercog et al, 2016 , Luiz et al, 2019 , Walters et al, 2019 ). The AAV vectors are commonly used in optogenetic experiments, as well as for the delivery of a plethora of probes to monitor neuronal activity.…”
Section: Methodsmentioning
confidence: 99%
“…2 Aiii): transgenes inserted in recombinase-dependent viral vectors are injected, via the same routes used for normal AAV injections in transgenic animal lines where the Cre expression is restricted to specific neuronal subpopulations ( Schnütgen et al, 2003 ). This strategy has been massively used to dissect the role of specific subsets of sensory neurons in the transmission of different innocuous and painful signals in the DRG ( Luiz et al, 2019 , MacDonald et al, 2021a , Walters et al, 2019 ). Transgenic targeting has been achieved in animals ranging from Drosophila to rodents and large mammals, including primates ( Guo et al, 2009 , O’Shea et al, 2017 , Pologruto et al, 2004 , Wang et al, 2003 ).…”
Section: Methodsmentioning
confidence: 99%